Effectiveness of Okra (Abelmoschus esculentus (L.) Moench) as an Ethnomedicine Based Anticancer Agent through Teratogenic Risk Testing - Syarifah Riska Mela Putri; Rahmi (JURNAL BIOSAINS, 2026)
Okra (Abelmoschus esculentus L.) contains lectin compounds known for their potential anticancer properties. However, limited research has examined its possible teratogenic effects—adverse impacts that may cause fetal abnormalities. The urgency of this study lies in assessing the safety of okra extract as a natural anticancer candidate. This research aimed to evaluate the teratogenic effects of okra fruit extract using an in vivo model as a preliminary step toward developing safe ethnomedicine-based anticancer agents. The study employed a Completely Randomized Design (CRD) with one control and three treatment groups. Female mice (Mus musculus L., DDW strain) received 2%, 4%, and 6% ethanol extracts of okra orally at a dose of 0.01 mL/g body weight daily from gestation days 0–10. The control group received no extract. Observations included maternal and fetal body weights, number of fetuses, liver morphology, and congenital malformations such as cleft palate and hydrocephalus. Data were analyzed using ANOVA (p < 0.05) followed by Bonferroni Post Hoc tests in SPSS version 23. The results showed that okra extract significantly affected maternal weight, fetal number, and fetal weight, as well as liver morphology and cleft palate incidence. These findings indicate that although okra exhibits anticancer potential, its teratogenic risks must be carefully evaluated.